Preparation of primary amine-terminated polybutadiene from cis-polybutadiene. (5th June 2021) - Xu, Li; Jie, Suyun; Bu, Zhiyang; Li, Bo-Geng
Graphical abstract: Highlights: Primary amine-terminated polybutadiene was prepared from cis -polybutadiene. High cis 1, 4-structure of polybutadiene was always maintained during all reactions. Mn of these telechelic polymers is controllable between 600 and 8000 g/mol. Abstract: As a telechelic polymer, the primary amine-terminated cis -polybutadiene (AmTPB) has a wide application prospect due to its active hydrogens in both end groups and high cis 1, 4-chain structure. In this work, the AmTPB with high cis -1, 4 content (>96%) was prepared for the first time by taking cis -polybutadiene as a starting material. Firstly, the aldehyde-terminated polybutadiene (ATPB) in a molecular weight range of 600–8000 g/mol was successfully synthesized by oxidative degradation of epoxidized polybutadiene prepared by reaction-controlled phase-transfer catalysis. After a simple post-processing, the AmTPB was prepared via two steps, i.e. the efficient synthesis of oxime-terminated polybutadiene (OTPB) from ATPB and the subsequent selective reduction of OTPB. The results showed that the high cis 1, 4-chain structure of polybutadiene did not change in all the reactions.